2012
DOI: 10.1210/jc.2011-2221
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid Drug-Induced Hematopoietic Damage: A Retrospective Cohort Study of Agranulocytosis and Pancytopenia Involving 50,385 Patients with Graves' Disease

Abstract: This study showed that ATD cause hematopoietic changes, which are occasionally severe and potentially fatal. The pathogenesis of agranulocytosis and pancytopenia might overlap, and additional studies are warranted to clarify this and to establish an optimal treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 17 publications
4
97
2
6
Order By: Relevance
“…[14][15][16][17][18][19][20] In studies done by Watanabe, Andres and Tamai, GCSF shortened the recovery period from agranulocytosis. 1,16,18,19 GCSF was ineffective against ATD-induced agranulocytosis in a prospective controlled study. 15 The cost of GCSF is also an important issue for both the patient and physician, particularly in emerging countries such as the Philippines.…”
Section: ê Sample Sizementioning
confidence: 95%
See 3 more Smart Citations
“…[14][15][16][17][18][19][20] In studies done by Watanabe, Andres and Tamai, GCSF shortened the recovery period from agranulocytosis. 1,16,18,19 GCSF was ineffective against ATD-induced agranulocytosis in a prospective controlled study. 15 The cost of GCSF is also an important issue for both the patient and physician, particularly in emerging countries such as the Philippines.…”
Section: ê Sample Sizementioning
confidence: 95%
“…1 The ATDs are associated with a variety of minor side effects as well as potentially life-threatening complications such as agranulocytosis. 2 Agranulocytosis is defined as an ANC of less than 500 cells/µL or 0.5 x 10 9 , which carries a very high risk for infection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its incidence, however, was much lower than that of agranulocytosis. To date, there were only 42 cases of ATD-induced aplastic anemia reported [15][16]. It has been suggested that the most likely mechanism for ATD-induced aplastic anemia was also an autoimmune humoral reaction against myeloid stem cells rather than granulocyte progenitor cells and mature circulating neutrophils [2,[17][18].…”
Section: Clinical Characteristicsmentioning
confidence: 99%